2015
DOI: 10.1155/2015/841213
|View full text |Cite
|
Sign up to set email alerts
|

Seedling Performance Associated with Live or Herbicide Treated Tall Fescue

Abstract: Tall fescue is an important forage grass which can host systemic fungal endophytes. The association of host grass and endophyte is known to influence herbivore behavior and host plant competition for resources. Establishing legumes into existing tall fescue sods is a desirable means to acquire nitrogen and enhance the nutritive value of forage for livestock production. Competition from existing tall fescue typically must be controlled to ensure interseeding success. We used a soil-on-agar method to determine i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 52 publications
(60 reference statements)
0
3
0
Order By: Relevance
“…Sod-seeding in ryegrass at an initial sward coverage above 10% did not allow a successful red clover seedling establishment in our study, neither in late summer, nor in early spring. Previous trials (9) in the same region showed that ryegrass sward renovation by sod-seeding or wet-seeding was successful only in fields with >50% bare soil, and although new ryegrass plants established, no improvements were measurable in total forage yield [28]. The authors concluded that sward renovation might only be profitable when forage yield and quality are improved, with the least costs for labor and seeds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sod-seeding in ryegrass at an initial sward coverage above 10% did not allow a successful red clover seedling establishment in our study, neither in late summer, nor in early spring. Previous trials (9) in the same region showed that ryegrass sward renovation by sod-seeding or wet-seeding was successful only in fields with >50% bare soil, and although new ryegrass plants established, no improvements were measurable in total forage yield [28]. The authors concluded that sward renovation might only be profitable when forage yield and quality are improved, with the least costs for labor and seeds.…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly used legume species in Northern Europe and Northern America are red clover (Trifolium pratense L.), white clover (Trifolium repens L.), and alfalfa (Medicago sativa L.), which mainly contribute with potential nitrogen fixation, stabilization of forage dry matter and increasing forage protein content [3,4,7]. However, introducing legumes can be very challenging, particularly in well-established stands where competition is strong [8,9]. Such stands may have a good sward coverage (e.g., >75%) across the field, and some phytotoxins may be released through the living grass roots to prevent germination and root growth of legume seedlings [10] or through the decomposition of grass killed by ice-encasement [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation